Antibacterial and antiplasmodial properties of chemical compounds isolated from bark of phyllanthus acidus (l.) skeels - Tan, Siow-Ping (Tanjung Malim, 2021)
Antibacterial and antiplasmodial properties of chemical compounds isolated from bark of phyllanthus acidus (l.) skeels by Tan, Siow-Ping